Cho hệ phương trình (( (( ((2)(3)) )^(2x - y)) + 6(( ((2)(3)) )^(((2x - y))(2))) - 7 = 0 (3^(((log )_9)( (x - y) ))) = 1 right. ). Chọn khẳng định đúng?


Câu 50783 Thông hiểu

Cho hệ phương trình \(\left\{ \begin{array}{l}{\left( {\dfrac{2}{3}} \right)^{2x - y}} + 6{\left( {\dfrac{2}{3}} \right)^{\dfrac{{2x - y}}{2}}} - 7 = 0\\{3^{{{\log }_9}\left( {x - y} \right)}} = 1\end{array} \right.\). Chọn khẳng định đúng?


Đáp án đúng: b

Phương pháp giải

Biểu thức \(y = {\log _a}f\left( x \right)\) xác định nếu \(f\left( x \right)\) xác định và \(f\left( x \right) > 0\).

Xem lời giải

...